Students’ Perception of Using Gamification as Media Review in English Learning - AKBARANI, RIZQI; Pamungkas, Firdaus D (New Language Dimensions, 2024)
Currently, technology has been involved in the learning process, especially English language learning. Technology has always been an important part of English teaching and learning. One of type technology that educators like is games.  In learning technology, the term gamification appears that be used in the learning process. Gamification is the integration of game aspects and mechanics into situations that are not inherently game-related, and it has shown considerable potential in increasing motivation, engagement, and educational achievements across diverse domains, such as language learning. Kahoot, Quizziz, and Bamboozle are examples of gamification that can be used in learning English especially to review material after the learning process. In this research, researchers wanted to investigate the students’ perception of using gamification tools Kahoot, Quizziz, and Bamboozle as media review after the English language learning process. This research used a descriptive quantitative method. The method of collecting data used a questionnaire where researchers needed 50 students as a sample to answer the questionnaire. From the research findings and discussion, researchers concluded that the use of gamification Kahoot, Quizziz, and Bamboozle increases students’ motivation and understanding of learning materials. The use of gamification Kahoot, Quizziz, and Bamboozle for material review is needed in English language learning where students can; make students easier to do English assignments during tests; make students more confident to learn English; and provide challenges for students to learn English. Furthermore, researchers also found that Kahoot is the most favorite gamification tool as a review media in English language learning.